A fuzzy queueing based model for controlling power demand of electric vehicle charging - Baloglu, Ulas Baran; Demir, Yakup (CEUR-WS, 2017)
The rapid penetration of electric vehicles may lead to peak problems in a traditional grid so that some of the smart grid research is focused on charging strategies for electric vehicles. The charging problem is suitable for using a queue structure, and fuzzy queueing can be implemented for this purpose. This paper presents a fuzzy queueing based model, which can also control the power demand of electric vehicle charging. A charging model should guarantee that all charging requirements can be satisfied before vehicles leaving the charging stations. Simulation results exhibit that the proposed model decreases average waiting time of vehicles and also the proposed model utilize charging stations better than a traditional queueing model. Copyright © 2017 held by the authors.
2017 Symposium for Young Scientists in Technology, Engineering and Mathematics, SYSTEM 2017 -- 28 April 2017 -- Kaunas -- 128043
Keywords: Electric vehicles; Fuzzy queueing; Smart grid